Bamboleio para além do rodar: processos de ensino-aprendizagem com o bambolê a partir de uma perspectiva circense contemporânea - Polizzelli, Gabrielle Lei [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
This research aims to report about, reflect on and develpo pedagogical possibilities for teaching hula hoop through a contemporary circus perspective. The work comprises three distinct, but interdependent parts. The first one, of a theoretical nature, enables the indentification of aesthetic and poetic elements of the so-called contemporary circus, analyzing its social and historical context of estabilishment, and the focus on the range of creative possibilities generated from the subjective and bodily individualities of the artists found in it. The second part consists of personal reports of hula hoop lessons taught by me, reflecting on the pedagogical tools used, and what results and reflections arose through these. The last part consists of a personal report as a student of three hula hoop teachers and a subsequente interview with them, in order to experience their specific didatics and understand their diferente view about circus and specifically about hula hoop practice.

A presente pesquisa tem como objetivo relatar sobre, refletir acerca de e elaborar possibilidades pedagógicas para o ensino do malabares-bambolê através de uma perspectiva circense contemporânea. O trabalho é composto por três etapas, distintas, porém interdependentes. A primeira, de cunho teórico, possibilita a identificação de elementos estéticos e poéticos do chamado circo contemporâneo, analisando seu contexto social e histórico de estabelecimento, e o enfoque na amplitude de possibilidades criativas geradas a partir das individualidades subjetiva e corporal dos artistas encontradas nesse. A segunda etapa consiste em relatos pessoais de aulas de bambolê ministradas por mim, refletindo sobre as ferramentas pedagógicas utilizadas, e quais resultados e reflexões surgiram através destas. A última etapa é constituída do relato pessoal como aluna de três professoras de bambolê e posterior entrevista com as mesmas, a fim de vivenciar suas didáticas específicas e entender suas diferentes visões acerca do circo e mais especificamente do bambolê.
Hooping beyond spinning: teaching-learning hooping processes from a contemporary circus perspective
Keywords: Malabarismo; Circos; Artistas circenses; Arte Estudo e ensino